2017
DOI: 10.1016/j.hpb.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medical or surgical admission on outcomes of patients with acute cholecystitis

Abstract: Patients under 70 years old with AC undergoing cholecystectomy admitted to MS had increased LOS, delay to the operation, and hospital costs compared to those admitted to a SS. Admission of patients with AC to a SS needs to be emphasized to reduce costs and improve quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Medical patients (ie, patients admitted to the hospital for an acute medical condition) are very different from surgical patients who are admitted to the hospital to undergo a procedure. 12 , 13 Planned surgical procedures offer an opportunity for preoperative interventions to reduce a patient’s risk of adverse outcomes after surgery. Examples include “prehabilitation” and Enhanced Recovery After Surgery (ERAS) programs.…”
mentioning
confidence: 99%
“…Medical patients (ie, patients admitted to the hospital for an acute medical condition) are very different from surgical patients who are admitted to the hospital to undergo a procedure. 12 , 13 Planned surgical procedures offer an opportunity for preoperative interventions to reduce a patient’s risk of adverse outcomes after surgery. Examples include “prehabilitation” and Enhanced Recovery After Surgery (ERAS) programs.…”
mentioning
confidence: 99%
“…The authors believe that this is a testament of the robustness of a dedicated gastrointestinal bleeding service. For several other conditions which were historically of a surgical nature, such as gallstone pancreatitis, 28 acute cholecystitis 29 and small bowel obstruction due to adhesions, [30][31][32] admission under a ) †Hypotension = defined as systolic blood pressure < 100 mmHg. ‡Critical care unit admission = defined as admission to a high dependency or intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believe that this is a testament of the robustness of a dedicated gastrointestinal bleeding service. For several other conditions which were historically of a surgical nature, such as gallstone pancreatitis, 28 acute cholecystitis 29 and small bowel obstruction due to adhesions, [30][31][32] admission under a surgical discipline were associated with decreased morbidity and mortality. [28][29][30][31][32] Aquina et al, who investigated the impact of admission discipline for patients with adhesive small bowel obstruction postulated that the differences in outcomes between a medical and surgical admission might be due to a reduced time to surgical intervention for patients that were initially managed by surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…20 Medical patients with surgical complications have an increased mortality and length of stay compared with medical patients with no surgical pathology; this could be attributed to multiple factors: patients having multiple organ systems involvement; being more unwell at presentation with higher CRP and poorer kidney function; and being treated by a team that lacks the expertise to diagnose and treat surgical problems. 21 Interestingly, medical patients with surgical pathology also have poorer prognosis than patients only presenting with emergency general surgical pathology. Previous studies reported mortality rates between 15% and 23% in patients undergoing emergency general surgical intervention.…”
Section: Meaning Of the Study: Possible Mechanisms And Implications F...mentioning
confidence: 99%